2010
DOI: 10.1111/j.1465-7295.2009.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the River Spill Over? Estimating the Economic Returns to Attending a Racially Diverse College

Abstract: "This article evaluates the frequently argued but heretofore little tested hypothesis that increasing minority representation in elite colleges generates tangible benefits for majority-race students. Using data on graduates of 30 selective universities, we find only weak evidence of any relationship between collegiate racial composition and the postgraduation outcomes of white or Asian students. Moreover, the strongest evidence we uncover suggests that increasing minority representation by lowering admission s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…On one front, several papers attempted to empirically examine the educational benefits of attending racially diverse colleges. For example, Black, Daniels, and Smith (2001) found a positive relationship between the proportion of blacks in the college attended and the postgraduate earnings in the National Longitudinal Survey of Youth; Arcidiacono and Vigdor (2010), using information on graduates of 30 selective universities in the College and Beyond data, found only weak evidence of any relationship between collegiate racial composition and postgraduation outcomes of white or Asian students. 3 Duncan, Boisjoly, Levy, Kremer and Eccles (2006), exploiting conditionally random roommate assignment at one large public university, found that cross-racial exposure influences individual attitudes and friendship patterns.…”
Section: Introductionmentioning
confidence: 99%
“…On one front, several papers attempted to empirically examine the educational benefits of attending racially diverse colleges. For example, Black, Daniels, and Smith (2001) found a positive relationship between the proportion of blacks in the college attended and the postgraduate earnings in the National Longitudinal Survey of Youth; Arcidiacono and Vigdor (2010), using information on graduates of 30 selective universities in the College and Beyond data, found only weak evidence of any relationship between collegiate racial composition and postgraduation outcomes of white or Asian students. 3 Duncan, Boisjoly, Levy, Kremer and Eccles (2006), exploiting conditionally random roommate assignment at one large public university, found that cross-racial exposure influences individual attitudes and friendship patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The identification concerns of the previous two papers are present here as well, 40 , and their estimates are large and negative, though statistically insignificant. Arcidiacono and Vigdor (2010) show that the estimated negative effects are being driven by the concentration of URM students at the bottom of the academic performance distribution. Namely, they split URM share into three groups: those with SAT scores more than 160 points above the student's SAT score, within 160 points, and below 160 points.…”
Section: Earningsmentioning
confidence: 99%
“…4 Justice Sandra Day O'Connor's majority opinion from 2003 in the Grutter v. Bollinger case cites some evidence in support of the claim that there are educational benefits to racial diversity. However, the evidence from economics on the effects of diversity at the institution level is more mixed (Arcidiacono and Vigdor, 2010;Daniel et al, 2001;Hinrichs, 2011). Studies by economists based on randomly assigned roommates or peer groups generally find positive effects of cross-racial interaction (Baker et al, 2011;Boisjoly et al, 2006;Camargo et al, 2010;Carrell et al, 2016), although it is unclear whether this result has external validity for predicting the effects of changing the level of diversity of an entire student body.…”
Section: Introductionmentioning
confidence: 99%
“…34 There are large challenges even in estimating the main effect of diversity at the college level. Arcidiacono and Vigdor (2010), Daniel et al (2001), and Hinrichs (2011) have all done so and have found mixed results, although there may be concern about selection bias. Affirmative action bans may be useful for identifying the effects of diversity, but they likely also change the ability level of the student body and so cannot necessarily be used to identify the effects of diversity net of ability.…”
mentioning
confidence: 99%